Comparison of genotypes of opaque black common bean in acid soils of southern Veracruz - Tosquy-Valle, Oscar Hugo; Zetina-Lezama, Rigoberto; López-Salinas, Ernesto; Ibarra-Pérez, Francisco Javier; Villar-Sánchez, Bernardo; Rodríguez-Rodríguez, José Raúl (REVISTA TERRA LATINOAMERICANA, 2020)
In southern Veracruz, Mexico, soil acidity is one of the main environmental factors that reduce the production yield of common bean. The objectives of this research were to identify outstanding opaque black bean breeding lines according to their level of adaptation to acid soils and high yield eff iciency with and without the addition of dolomite into the soil, as well as to determine which is the yield component that associates the most to a greater production of beans. During the Fall/Winter season of 2016-17 two trials were performed in Juan Rodríguez Clara, Veracruz, in a land with a soil of initial pH = 4.67. One trial was conducted under stress conditions by soil acidity and the other with 2.58 Mg ha-1 of dolomite, applied to the soil 27 d before sowing. Twelve black bean breeding lines were evaluated and compared to Negro Grijalva and Negro Comapa bean varieties. All beans were arranged in a randomized complete block design with three replicates. The variables measured were dry matter production without grain, weight of 100 seeds, number of pods per plant and grain yield. An analysis of variance of the quantif ied variables and the least signif icant difference (LSD, 0.05) tests for separation of means were performed. Negro Citlali/XRAV-187-3-1-8 showed the best adaptation to acid soil conditions in southern Veracruz, which obtained yields of 911.0 and 706.3 kg ha-1 with and without dolomite, respectively. These values were signif icantly higher than the commercial beans. This breeding line also showed the highest productive eff iciency, since it obtained the highest geometric mean (MGi) values (802.1) and a relative eff iciency index (IERi) of 2.00. Under both conditions of edaphic acidity, the number of pods per plant was the only plant trait that was positively related to seed yield (r = 0.91 ** and 0.87 **, with and without dolomite).